2015
DOI: 10.1111/inr.12216
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff and their team: Impact on intention to leave

Abstract: This study illustrates the potential benefits of the positive influence of team-member exchange on key organizational attitudes of nursing staff, and the negative influence on intention to leave through affective commitment and job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
(73 reference statements)
1
14
0
1
Order By: Relevance
“…This is similar to a previous study (Bolino et al ; Dasgupta ; Trybou et al. ), which suggests that TMX, as the basis for organizational effectiveness, affects job satisfaction. We, therefore, confirmed that TMX is as important as LMX in nursing organizations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is similar to a previous study (Bolino et al ; Dasgupta ; Trybou et al. ), which suggests that TMX, as the basis for organizational effectiveness, affects job satisfaction. We, therefore, confirmed that TMX is as important as LMX in nursing organizations.…”
Section: Discussionsupporting
confidence: 92%
“…() in Korea and different from that of Woo & Shin () in Korea and Trybou et al. (). The reason why can be explained in two ways.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The importance of the relationships within the nursing team, when nurses experience high-quality exchanges with their fellow team members. As these relationships solidify, nurses become more satisfied with their job and feel a greater sense of belonging to the hospital, and this minimizes the nursing staff's intention to leave [19]. There are a number of nurses who believe that the image of the nursing profession is affected by many factors, such as what is displayed and published about nursing in the media and advertising, and each individual's level of education.…”
Section: Introductionmentioning
confidence: 99%
“…) and patient satisfaction (Mrayyan ), as well as in reducing nurses’ turnover intention (Trybou et al. ; Wang et al. ).…”
Section: Introductionmentioning
confidence: 99%